(untitled) (Jalalabad Medical Journal, 2026)
Congenital generalized lipodystrophy (CGL) or Berardinelli-Seip congenital lipodystrophy is a very rare genetic disorder, characterised by severe reduction to absence of adipose tissue. They presented with very typical characteristic features but diagnosis is often difficult and if undiagnosed, it can lead to several complications. We present a case of 5-year old Bangladeshi boy who presented to us due to abnormal facies and was diagnosed as congenital generalized lipodystrophy (CGL). Jalalabad Med J 2025; 22 (2): 92-95